Assessment of Knowledge, Attitude and Practice Regarding Single Use Plastics among the Residents of a Rural Area in a Coastal District of Karnataka - A Descriptive Study - Shaira, Habeena; Ismail, Imaad Mohammed; Ahmed, Nihal; Zeena, Noorul; Arooj, Peer; Shreya, Poojary; Shafir, Reiham; Nazeer, Rahima (National Journal of Community Medicine, 2020)
Background: The consumption of single-use-plastics is on the rise globally. This study was conducted to assess the knowledge, attitude and practice on single-use-plastics among the residents of a rural area in a coastal district of Karnataka. Methods: A cross-sectional study was conducted from April to June 2019 among the residents of Madani Nagar. Data was collected by interviewing any adult member of the house aged more than 18 years using a standardised application called Epicollect 5. Results: A total of 319 residents participated in the study. More than 70% were aware that single-use-plastics cause’s harmful effects on health but more than 95% were unaware that plastic causes global warming and climatic change in the environment. The attitude towards the single-use-plastic was satisfactory since 80% of them were of opinion that single-use-plastic should be banned and more than 60% were willing to replace the plastic bag with an alternative. Practice was found to be poor since 82.4% were using plastic bag on regularly basis. Conclusions: The overall knowledge regarding single-use-plastic was inadequate, attitude was favourable and practices were unsatisfactory. Awareness regarding single-use-plastics and its harm and strict enforcement of plastic ban is the need of the hour.